Памятники малополовецкого типа в бассейне р. Супой - Лысенко, С.Д.; Куштан, Д.П.; Панковский, В.Б.; Федько, В.Ф. (My University, 2011)
Лисенко С. Д., Куштан Д. П., Панковський В. Б., Фєдько В. Ф. Пам’ятки малополовецького типу в басейнi р. Супой У статті розглянуто пам’ятки із керамікою малополовецького типу тшинецького культурного кола, розташовані у середній течії р. Супой. Наведено характеристику досліджених об’єктів, крем’яної та кістяної індустрій. Простежено два етапи розвитку малополовецької кераміки: ранній, співіснуючий із пізніми проявами культурного кола Бабине, та пізній, синхронний ранньому етапу бережнівсько-маївської зрубної культури. S. Lysenko, D. Kushtan, V. Pankovskiy, V. Fedko. sites of Malopolovetske Type on supoi The article discusses new settlement sites that contain pottery of Malopolovetske type of Trzciniec cultural circle. Those sites are situated on the right bank of Supoi, along its middle flow. Co-authors characterize some objects, lithic and bone industries discovered and investigated there. Two stages in the development of the pottery of Malopolovetske type were stated by them. Early one was contemporaneous to the latest manifestations of Babine cultural circle; they synchronize later stage to the first period of Berezhnovka-Maiovka culture.
Keywords: Середнє Подніпров’я; малополовецький тип; кістяна індустрія; Middle Dnipro region; Malopolovetske type; bone industry